“We are in the forgotten corner!” a qualitative study of experiences and challenges among Chinese older women at the onset of acute myocardial infarction - Yu, Huidan; Liu, Huafen; An, Zifen; Zhou, Jiali; Meng, Xianmei; Luo, Xianwu; Zhou, Xiaoyang (Frontiers in Public Health, 2023)
Background: Acute myocardial infarction (AMI) is a common and serious cardiovascular disease (CVD) that is one of the leading causes of death among women globally and in China. However, there are gender differences and inequalities in the detection and management of AMI, especially in older people. Few research could demonstrate how challenges and barriers affect older women’s help-seeking behavior and process in China. Purpose: The objective of this study was to explore the experiences of older women with AMI, focusing on their perception, challenges, and coping strategies at the onset of AMI in Wuhan, China. Results: Interpretative Phenomenological Analysis (IPA) was used in this study to analyze the data on 18 participants and three major themes were generated: disease perception disorder, negative coping strategies, and barriers to social-environmental context. Conclusion: To reduce older women’s delay in seeking help, healthcare professionals should provide public health education that emphasizes gender-related disparities, and age-specific knowledge-attitude aspects to high risk groups. Policy-based and health administration recommendations, including e-health information support, access to care, and social-environmental factors, should be highlighted to promote women’s health behavior. Key Words: myocardial infarction; gender; experience; challenges; older people; qualitative